A expansão do setor sucroenergético em território indígena no sul de Mato Grosso do Sul-Brasil. - Marine Dubos-Raoul (Confins)
Since the beginning of the 21st century, Brazil has experienced a significant increase in the production of sugarcane in its territory. The southern region of the state of Mato Grosso do Sul has specialized in sugarcane production since 2006. In particular, the region of Dourados is a region with a strong indigenous population, which witnessed the loss of its territories during the 20th century, giving rise to conflict between indigenous peoples and rural producers. Thus, the arrival of the sugarcane industry reactivates old tensions and tends to redefine the strategies of indigenous struggles for the claim of their tekoha (Indigenous Territory).Since the beginning of the 21 st century , Brazil has experienced a significant increase in the production of sugarcane in its territory . The southern region of the state of Mato Grosso do Sul has specialized in sugarcane production since 2006. In particular, the region of Dourados is a region with a strong indigenous population, which witnessed the loss of its territories during the 20th century , giving rise to conflict between indigenous peoples and rural producers. Thus, the arrival of the sugarcane industry reactivates old tensions and tends to redefine the strategies of indigenous struggles for the claim of their tekoha (Indigenous Territory ).